2021
DOI: 10.3390/plants10102167
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Macronutrient Uptake and Removal by Modern Peanut Cultivars

Abstract: The productive potential of new peanut cultivars has increased over the years in relation to old cultivars, especially when compared with ones with upright growth habit. Thus, the requirement for macronutrients for these new cultivars may also have increased, making the existing fertilizer recommendation tables obsolete, thus increasing the need for further studies measuring the real macronutrient requirements of these new peanut cultivars. Our study aimed to evaluate the growth patterns and the macronutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…We recommend that the response of peanut plants to K application needs to be further studied, as the rates applied are lower than the exported amounts, likely due to peanut ability to take up non‐exchangeable K from the soil (Xu et al., 2021). For yields between 5000 and 9000 kg ha −1 , K absorptions that vary from 175 to 280 kg ha −1 and between 100 and 200 kg ha −1 are exported via pods (Crusciol et al., 2021). Recommended or common rate in peanut in Brazil is 25 kg ha −1 and the Georgia is 74 kg ha −1 for soils with low‐K content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recommend that the response of peanut plants to K application needs to be further studied, as the rates applied are lower than the exported amounts, likely due to peanut ability to take up non‐exchangeable K from the soil (Xu et al., 2021). For yields between 5000 and 9000 kg ha −1 , K absorptions that vary from 175 to 280 kg ha −1 and between 100 and 200 kg ha −1 are exported via pods (Crusciol et al., 2021). Recommended or common rate in peanut in Brazil is 25 kg ha −1 and the Georgia is 74 kg ha −1 for soils with low‐K content.…”
Section: Discussionmentioning
confidence: 99%
“…The recommended plant density is 16.7 plants m −2 in Brazil (Zoz et al., 2019) and 14.3 plants m −2 in the United States (Oakes et al., 2020; Sarver et al., 2016), with increased inter‐plant competition for water and nutrients with increased plant density (Hatfield & Dold, 2019; Li et al., 2019). Peanut plants uptake per 1000 kg of K pods is about 30 kg with a K harvest index of about 50% (Crusciol et al., 2021) with about 210 kg ha −1 of K uptake and 140 kg removed in the pod harvest for 7000 kg ha −1 pod yield.…”
Section: Introductionmentioning
confidence: 99%
“…Estimation variation in nutrient requirement may be related to differences in planting regions, cultivars, soil conditions, yield level, and tillage [ 30 , 33 ]. Crucsiol et al [ 3 ] demonstrated that N absorption for older cultivars remains high, while newer cultivars were less demanding in N. Xie et al [ 25 ] found that the values of nutrient requirement simulated by modeling were lower than the average observed values, and they explained that the N, P, and K predicted by the model were the optimal nutrient requirements under the conditions of the balanced absorption of N, P, and K. However, high soil nutrient supply and excessive fertilization practices may have resulted in excess nutrient uptake [ 31 ]. A large number of studies have demonstrated that crop nutrient uptake positively correlates with yield level, but the yield increase decreases when the yield reaches a certain level [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen (N), phosphorus (P), and potassium (K) are essential nutrients for crops. Application of NPK fertilizer can improve crop yield [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation